2021
DOI: 10.1136/gutjnl-2021-324546
|View full text |Cite
|
Sign up to set email alerts
|

Single-cell sequencing unveils distinct immune microenvironments with CCR6-CCL20 crosstalk in human chronic pancreatitis

Abstract: ObjectiveChronic pancreatitis (CP) is a potentially fatal disease of the exocrine pancreas, with no specific or effective approved therapies. Due to difficulty in accessing pancreas tissues, little is known about local immune responses or pathogenesis in human CP. We sought to characterise pancreatic immune responses using tissues derived from patients with different aetiologies of CP and non-CP organ donors in order to identify key signalling molecules associated with human CP.DesignWe performed single-cell l… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 60 publications
0
12
0
Order By: Relevance
“…In contrast, an enormous immune cell population was detected in the CP group, including B cells, T cells, plasma cells, macrophages, and neutrophils. According to Lee et al鈥檚 study, T cells are the major immune cell type in the pancreas of CP patients [ 14 ]. The overabundant B cells and plasma cells in the CP group could be caused by species differences or modeling methods.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, an enormous immune cell population was detected in the CP group, including B cells, T cells, plasma cells, macrophages, and neutrophils. According to Lee et al鈥檚 study, T cells are the major immune cell type in the pancreas of CP patients [ 14 ]. The overabundant B cells and plasma cells in the CP group could be caused by species differences or modeling methods.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Tosti et al utilized single nuclear RNA sequencing (snRNA-seq) to generate transcriptome profiles of the pancreas from healthy neonates, healthy adults, and CP patients [ 12 ]. Single-cell analyses by Blobner et al demonstrated two unique clusters of acinar cells in human CP [ 13 ], and Lee et al鈥檚 study revealed distinct immune microenvironments in human hereditary and idiopathic CP [ 14 ]. These findings contribute to our understanding of the complex pancreatic genomic landscape and the cellular foundations of CP.…”
Section: Introductionmentioning
confidence: 99%
“…CCR6 has also been related to chronic pancreatitis in a single-cell sequencing analysis with pancreatic immune cells. Single-cell sequencing revealed that the CCR6/CCL20 axis is upregulated in hereditary chronic pancreatitis when compared with idiopathic chronic pancreatitis; therefore, this signaling pathway could be a potential target in human hereditary chronic pancreatitis [ 69 ].…”
Section: Diseases Associated With Ccr6mentioning
confidence: 99%
“…Single-cell sequencing of pancreatic immune cells isolated from hereditary and idiopathic chronic pancreatitis (CP) patients undergoing total pancreatectomy has revealed reduced T-cell clonicity in hereditary CP, and C-C motif chemokine receptor 6 (CCR6) ligand (CCL20) expression is significantly upregulated in monocytes of hereditary CP. The CCR6-CCL20 signaling pathway may be used as a potential therapeutic target for human inherited CP ( 34 ). The detection of TCR+ macrophages, proliferative macrophages, and natural killer dendritic cells in peritoneal fluid of endometriosis by single-cell sequencing suggests that immune dysfunction occurs in the peritoneal fluid of endometriosis and provides a valuable tool for the future development of immunotherapy ( 35 ).…”
Section: Chronic Inflammatory Diseasesmentioning
confidence: 99%